IDENTIFIKASI MODAL SOSIAL PADA PROGRAM PEMBERDAYAAN MASYARAKAT MISKIN MELALUI DANA ZAKAT, INFAK DAN SEDEKAH - Agustin, Atut Frida; Ashar, Khusnul; Multifiah, Multifiah (IQTISHODUNA, 2013)
Paradigma based on this research is naturalistic paradigm sourced from phenomenologist which more criticize on positivism approach which considered to rigid, black and white, also toomuch obeying the concept. According to knowledge paradigm an social science also problem to be answered in this research, the research uses qualitative approach. The research finding are: 1) people empowerment in Sumberoto village based on Islamic religious values, they are believing, purity, and ukhuwah islamiah (Islam brotherhood). This model is also built by trust and norm (rule) in society with reciprocal relations. While system used is network, with voluntary, similarity, freedom, and civilization, moved by proactive all empowerment management. 2) moral value reflected in social capital and religious value has played role in producing poor people empowerment model more fair, independence, honorable, and continued without losing humanity. That’s the poor people empowerment model which became this research’s thesis.